Determinants of Egyptian Banking Sector Profitability: Time-Series Analysis from 2004- - Heba Youssef Hashem (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - The purpose of this paper is to examine the determinants of banking sector profitability in Egypt to shed light on the most influential variables that have a significant impact on the performance of this vital sector. Design/methodology/approach - The analysis includes a time series model of quarterly data from 2004 to 2014. The model utilizes Cointegration technique to investigate the long-run relationship between the return on equity as a proxy for bank profitability and several bank-specific variables including liquidity, capital adequacy, and percentage of non-performing loans. In addition, Vector Error Correction Model (VECM) is utilized to explore the short-run dynamics of the model and the speed of adjustment to reach the long-run equilibrium. Findings - The main findings of this work show that banking sector profitability is inversely related to capital adequacy, the percentage of loan provisions and the ratio of deposits to total assets. On the other hand, it is positively related to the size of the banking sector which implies that the banking sector exhibits economies of scale. Research limitations/implications - The implications of this work is that it helps reveal the major factors affecting bank performance in the short-run and long-run, and hence provide bank managers and monetary policy makers with beneficial insights on how to enhance bank performance. Since the banking sector represents one of the main engines of financing investment, enhancing the efficiency of this sector would contribute to economic growth and prosperity. Originality/value - The Vector error correction model showed that about 4% of the disequilibrium is corrected each quarter to reach the long run equilibrium. In addition, all bank specific variables were found to affect profitability in the long-run only. This study would serve as a base that further work on Egyptian banking sector profitability can build on by incorporating more variables in the analysis or investigating other types of econometric models.
Keywords: G21; C22; 330; Bank Profitability; Bank Performance; Determinants; Egypt; Time Series Analysis